A comparison study of sessile benthic community of coral reefs between Benuang Bay and Renggis Island, Tioman - Khodzori, Mohd. Fikri Akmal; Saad, Shahbudin; Hanapiah, Muhammad Faiz; Rahman, Mohammad Mustafizur (2012)
Study on the sessile benthic community of coral reefs has been carried out in Benuang Bay and Renggis Island from 15th to 17th September 2012. Coral Video Transect (CVT) method was used to record images of substrates along five 20 m transects at 3 – 5 m depth and 8 – 10 m depth in both study areas. The community was characterized using lifeform categories which provide a morphological description of the reef community. Results showed that a total 13 lifeform categories were identified in both sites. The total coral coverage in the Renggis Island (69.1%) was higher compared to Teluk Benuang (41.9%). Soft coral, Acropora branching, coral foliose and coral massive had shown high significant different between two sampling locations. High significant different were also observed between algae and coralline algae at 5m depth and 10m depth and also between both sampling sites. No significant different was observed between other invertebrates at different depth.